PENGEMBANGAN MEDIA MONOPOLI KEBUDAYAAN (POLDA) KOLABORASI DENGAN MODEL PEMBELAJARAN JIGSAW DALAM MENINGKATKAN SELF-CONFIDENCE SISWA KELAS V SEKOLAH DASAR - Nisa, Puput Saidatun; Amalia, Shofi Nur; Fatih, Mohamad (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to enhance the self-confidence of fifth-grade students at SDN Panggungrejo 06, Blitar Regency, through the development of an innovative learning medium called Monopoli Budaya (POLDA) with the theme “My Proud Region,” integrated with the Jigsaw learning model. The research adopted the Borg and Gall development model, which includes the stages of identifying potentials and problems, data collection, product design, design validation, design revision, and product testing. This study employed a Research and Development (R&D) approach. Data were collected through observation, interviews, expert validation questionnaires, and student self-confidence questionnaires. The results of expert validation indicated that the POLDA media was feasible and practical for classroom use, achieving 98% for media validation and 73% for material validation. Furthermore, students’ self-confidence increased significantly after using the POLDA media integrated with the Jigsaw model, as evidenced by product trial results. In conclusion, the development of the Monopoli Budaya cooperative learning medium effectively fosters students’ self-confidence and engagement in learning science and social concepts in elementary school